One-step cold-induced aqueous two-phase system for the simultaneous determination of fipronil and its metabolites in dietary samples by liquid chromatography–high resolution mass spectrometry and the application in Total Diet Study. (30th March 2020) - Li, Shaohua; Chen, Dawei; Lv, Bing; Li, Jingguang; Zhao, Yunfeng; Wu, Yongning
Highlights: One-step enhanced sensitivity and effective cleanup strategy was developed. A larger linear dynamic range was achieved by LC-HRMS using tSIM acquisition mode. Phospholipids can be effectively reduced by CI-ATPS coupled with DSPE procedures. The method was validated and applied in a proficiency test and dietary samples. Abstract: Herein, a cold-induced aqueous two-phase system (CI-ATPS)-based concurrent sample enrichment and cleanup strategy was developed for the analysis of fipronil and its metabolites in dietary samples by liquid chromatography–high resolution mass spectrometry. By optimizing the conditions in CI-ATPS, the analytes were extracted to a small volume acetonitrile-rich phase with the enrichment factor of three-folds. Additionally, the lipids could be efficiently precipitated between the lower and upper layer to complete the removal of lipids. In detection analysis, a target single ion monitoring mode was employed to enhance the detection capability of fipronil and its metabolites. Generally, this established method could detect the target analytes in dietary samples at ng/kg level. Finally, this method was validated and certificated by a proficiency test, then was also successfully applied to dietary samples in the Total Diet Study, and the results showed that 56.3% of samples were detected with fipronil or its metabolites.